User Centered Design of Interaction Techniques for VR-Based Automotive Design Reviews - de Clerk, Matthias; Dangelmaier, Manfred; Schmierer, Gernot; Spath, Dieter (Frontiers in Robotics and AI, 2019)
The exterior design is one of the most important selling propositions in the automotive premium market. Because of progressing digitization in the automotive industry, it is increasingly assessed using virtual 3D models. In this context, Virtual Reality (VR) is a key technology of continuously growing importance. However, complicated interaction in VR proves to be a major drawback in industrial settings. In this paper, we report insights of our user centered approach aiming at appropriate VR interaction techniques supporting designers, engineers, and management executives optimally in design assessment. Our approach splits into two iterations according to the main interaction tasks Visual Inspection and Model Comparison. In each iteration, alternative interaction techniques were conceptualized, implemented as prototypes, and evaluated in a user study in terms of Usability, User Experience, Intuitiveness and Task Load. In the first iteration six interaction techniques for Visual Inspection, two speech-based, two gesture-based, and two touch-based variants, were studied. Incorporating the results, the second iteration explores three interaction techniques for Model Comparison utilizing (1) a portable touch remote, (2) hand and body gestures, and (3) a multimodal mix of both. The final concepts yielded high ratings by the participants, but showed significant differences between rational and emotional aspects. We conclude that the acceptance of VR in automotive design could be facilitated by refining and applying these interaction techniques.